Geographic space, assets, livelihoods and well-being in rural Central America: empirical evidence from Guatemala, Honduras and Nicaragua - Alwang, Jeffrey; Jansen, Hans G. P.; Siegel, Paul B.; Pichon, Francisco (International Food Policy Research Institute, 2005)
This paper uses an asset-base framework to analyze the determinants of rural growth and sustainable poverty reduction for the three poorest countries in Central America: Guatemala, Honduras and Nicaragua...Using a combination of GIS mapping techniques, quantitative household analysis, and qualitative analyses of assets and livelihoods, the authors generate a description of rural territories that recognizes the differential effects of policies and asset bundles across space and households. They identify the combinations of human, natural and physical, social and location-specific assets that matter most to raise household well-being and take advantage of prospects for poverty-reducing growth.